Android Application for Automatic Door Control System using Body Temperature Measuring Sensor - Iskandar, Dwi; Nugroho, Erik Wisnu; Wahyudi, Fiki; Kusuma, Junianto Candra; Ramadhani, Zulkifli (International Journal of Computer and Information System (IJCIS), 2023)
One way for people to prevent the transmission of Covid-19 in indoor and outdoor activities is by using body temperature detection. People who have a body temperature higher than the measurement limit are prohibited from mingling with other people because they have a high probability of being infected with the virus and can transmit it to other people. Manual checks in public places can cause officers to potentially contract the virus and can spread it to other visitors more quickly. Therefore, it is necessary to develop an automatic body temperature measurement system by displaying the results of the measurements on a screen and automatic door as a further prevention step, and temperature data can be stored in a database to help make the right decisions in preventing the spread of Covid-19 in that place. The implementation stages of the activities include: Data Collection, Preparation of Technology Design and Purchase of Materials, Product Manufacturing, Product Testing, Product Evaluation. An Android application for an automatic door control system using a body temperature measurement sensor can be developed into an even better tool. The development of this prototype will be developed by adding a PIR sensor and system modifications. The addition of a PIR sensor is used to increase the security of the tool to detect only human body temperature which can be recorded in order to minimize data errors. The system modifications made can be used for initial examination assessments with body temperature and also the addition of a system for measuring body weight and height to complete the assessment data.